Development of accounting in the history of modern Turkey (from 1923 to 2006) - (:unkn) unknown (Nova Science Publishers, Inc., 2011)
Considerable research has considered the past accounting experiences response to future accounting applications, but much of this research has taken place in western countries, particularly in the English-speaking nations. This research extends the existing literature by examining deeply the accounting history of modern Turkey, a country still considered to have a developing economy, began newly to negotiations with the E.U and waited for to be largest population of the E.U. Modern Turkey is the heritage of Ottoman Empire but a lot of change has been made as of passing from monarchy to democracy. Accounting applications and rules have got their share from this rooted change period. © 2010 by Nova Science Publishers, Inc. All rights reserved.